Gambaran Pengetahuan Bidan Terhadap Penanganan Bayi Baru Lahir Dengan Asfiksia di Rumah Sakit Khusus Daerah Ibu Dan Anak Pertiwi Makassar - Yenni Yenni; Andi Tenri Angka (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
Asphyxia is the failure to initiate and continue breathing spontaneously and regularly when the baby is born or some time after birth. The aim of the research is to determine the description of midwives' knowledge of the meaning of asphyxia, etiology and treatment of asphyxia at the Special Regional Hospital for Women and Children in Pertiwi Makassar. The research was carried out at the Special Regional Hospital for Women and Children in Pertiwi Makassar. The method in this research uses descriptive analytics by taking a sample of 45 midwives with a total sampling technique, namely all midwives who work at the Pertiwi Makassar Regional Special Hospital for Women and Children in 2016. The data used in this research is primary data with the variable studied being knowledge midwives about the meaning of asphyxia, the etiology of asphyxia and the treatment of asphyxia. The results of the research from 45 midwives who were willing to be respondents found 42 respondents (93.33%) who had good knowledge about the meaning of asphyxia, 42 respondents (93.33%) who had good knowledge about the etiology of asphyxia and 40 respondents (88.89%) who had good knowledge about the etiology of asphyxia. good about treating asphyxia. In conclusion, most of the midwives' knowledge is good about the meaning of asphyxia, the etiology of asphyxia and the treatment of asphyxia. It is hoped that midwives will further increase their knowledge, especially in handling asphyxia in newborns to reduce the neonatal mortality rate.